Downregulation of Transcriptional Activity, Increased Inflammation, and Damage in the Placenta Following in utero Zika Virus Infection Is Associated With Adverse Pregnancy Outcomes - Creisher, Patrick S.; Lei, Jun; Sherer, Morgan L.; Dziedzic, Amanda; Jedlicka, Anne E.; Narasimhan, Harish; Chudnovets, Anna; Campbell, Ariana D.; Liu, Anguo; Pekosz, Andrew; Burd, Irina; Klein, Sabra L. (Frontiers in Virology, 2022)
Zika virus (ZIKV) infection during pregnancy causes serious adverse outcomes to the developing fetus, including fetal loss and birth defects known as congenital Zika syndrome. The mechanism by which ZIKV infection causes these adverse outcomes, and specifically the interplay between the maternal immune response and ZIKV replication has yet to be fully elucidated. Using an immunocompetent mouse model of transplacental ZIKV transmission and adverse pregnancy outcomes, we have shown that ZIKV induces placental inflammation, including elevated secretion of IL-1β, which when pharmacologically blocked with an IL-1 receptor antagonist, reverses the adverse effects of in utero ZIKV infection. To determine if ZIKV increases placental IL-1β by innate sensing and activation of the NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome, we evaluated placental expression of IL1β signaling and NLRP3 inflammasome components, including IL-1β, NF-κB, NLRP3, and Caspase-1 after intrauterine ZIKV infection. Within 48 hours after ZIKV infection at embryonic day 10, viral RNA was detected in placentas and fetuses from ZIKA infected dams, which corresponded with placental damage and reduced fetal viability as compared with mock infected dams. Despite an increase in placental IL-1β within 3-6 hours post infection, there was no evidence of activation of the NLRP3 inflammasome. These results suggests that IL-1β activation and secretion in the placenta during ZIKV infection may be mediated by non-inflammasome pathways and cleavage by non-caspase-1 enzymes.